Licófitas Cormofíticas Arborescentes do Afloramento Quitéria Formação do Rio Bonito (Bacia do Paraná), RS - JASPER, ANDRÉ; GUERRA-SOMMER, MARGOT (Pesquisas em Geociências, 1998)
This study reports on a in situ lycopod assemblage of stumps and trunks from a sand-rich coaly section of the Rio Bonito Formation (Artinskian – Kungurian) in Rio Grande do Sul state. These dense tickets of arborescent forms have been found in situ; their cormose rooting systems are “non stigmarioid”. The variation observed, from elliptical (Brasilodendron type) to rhomboidal (Lycopodiopsis type) leaf cushion in the same specimen indicates that both can represent different levels in the same trunk. Considering that the South Brazilian coals are mainly hipoautochthonous, lycopods of Brasilodendron type could be dominants in the plant forming association of the peat.